Study design considerations in a large COPD trial comparing effects of tiotropium with salmeterol on exacerbations - Beeh, Kai-Michael (Dove Medical Press, 2009)
Currently available long-acting inhaled bronchodilators (tiotropium, salmeterol, formoterol) have demonstrated beneficial effects on exacerbations in placebo-controlled trials. However, there have been no direct comparisons of these drugs with exacerbations as the primary outcome and consequently COPD treatment guidelines do not indicate a preference for either bronchodilator. Therefore, an international, randomized, double-blind, double-dummy, parallel-group clinical trial has been designed to investigate the comparative efficacy of 2 long-acting bronchodilators tiotropium 18 μg daily and salmeterol 50 μg bid on exacerbations. The trial will include at least 6800 randomized patients with diagnosis of COPD, ≥ 10 pack-year history of smoking, post-bronchodilator FEV(1) ≤ 70% predicted, and a history of exacerbations in the previous year. The primary endpoint is time to first COPD exacerbation. Secondary endpoints include number of exacerbations and time to premature discontinuation of trial medication. The trial has been designed to address several of the challenges in studying exacerbations in a controlled trial by a symptom and event-based definition of exacerbations, frequent follow-up contacts, selection of time to first event as the primary endpoint and using exposure adjusted analysis when examining number of events. Other challenges in designing exacerbation trials such as differential discontinuation and follow-up of discontinued patients are discussed.